Population-based surveillance for cervical cancer precursors in three central cancer registries, United States 2009. - Flagg, Elaine W; Datta, S Deblina; Saraiya, Mona; Unger, Elizabeth R; Peters, Edward; Cole, Lauren; Chen, Vivien W; Tucker, Thomas; Byrne, Mary Jane; Copeland, Glenn; Silva, Won; Watson, Meg; et al. (Cancer Causes & Control, 2014)
Purpose: The USA has a well-established network of central cancer registries (CCRs) that collect data using standardized definitions and protocols to provide population-based estimates of cancer incidence. The addition of cervical cancer precursors in select CCR operations would facilitate future studies measuring the population-level impact of human papillomavirus (HPV) vaccine. To assess the feasibility of collecting data on cervical cancer precursors, we conducted a multi-site surveillance study in three state-wide CCRs, to obtain annual case counts and compare rates of precursor lesions to those for invasive cervical cancer.Methods: We developed standardized methods for case identification, data collection and transmission, training and quality assurance, while allowing for registry-specific strategies to accomplish surveillance objectives. We then conducted population-based surveillance for precancerous cervical lesions in three states using the protocols.Results: We identified 5,718 cases of cervical cancer precursors during 2009. Age-adjusted incidence of cervical cancer precursors was 77 (Kentucky), 60 (Michigan), and 54 (Louisiana) per 100,000 women. Highest rates were observed in those aged 20-29 years: 274 (Kentucky), 202 (Michigan), and 196 (Louisiana) per 100,000. The variable with the most missing data was race/ethnicity, which was missing for 13 % of cases in Kentucky, 18 % in Michigan, and 1 % in Louisiana. Overall rates of cervical cancer precursors were over sixfold higher than invasive cervical cancer rates [rate ratios: 8.6 (Kentucky), 8.3 (Michigan), and 6.2 (Louisiana)].Conclusions: Incorporating surveillance of cervical cancer precursors using existing CCR infrastructure is feasible and results in collection of population-based incidence data. Standardized collection of these data in high-quality registry systems will be useful in future activities monitoring the impact of HPV vaccination across states. As a result of this study, ongoing surveillance of these lesions has now been conducted in four CCRs since 2010.